SKIM PEMBIAYAAN UMKM DAN PENINGKATAN KINERJA UMKM FURNITURE JEPARA - Astiwi Indriani; Shoimatul Fitria (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2017)
The government has been doing a lot of efforts to help SMEs capitalisation, various schemes of credit and funding for SMEs were launched as KUR, PMT, Gapoktan, etc. In the middle of 2015, KUR could be just absorbed although the conditions have softened. This is because SMEs are unique, that is feasible but not bankable. In addition, the funding only limited on distributing capital, in fact the SMEs problems not only in the capital, but concerning the expertise in marketing, financing, and managing the company. It need deep research about how to formulate funding schemes that is considered attractive by the SMEs. This research used qualitative method with the interpretive paradigm fenomology approach, case study in PT Jepara Express International (furniture supplier). This research was conducted through interview, observation and documentation by using data analysis technique, Milles and Hubberman method. Credibility of data was tested by using triangulation techniques, data sources, and time. From research methods, SMEs furniture in Jepara intrepreting that funding considered attractive if using partnership type with cluster and profit-sharing systems are becoming solution for SMEs furniture’s funding distribution program. In addition, certain entities formed to become alternative distribution funding schemes. Through this entities, SMEs furniture in Jepara could access and also got assisstance in marketing, financing and managing the company. Finnally, SMEs furniture could increase its performance through assisstance program. In the future needs further research about appropriate entities to represent the SMEs needed in financing and assisstance